2018
DOI: 10.29332/ijhs.v2n2.158
|View full text |Cite
|
Sign up to set email alerts
|

Adult women perception towards obesity and its intervention strategies in the community

Abstract: Obesity was one of the health problems experienced in the society, especially in adult women and the number was increasing rapidly every year. The various factors contribute to the obesity occurrence in adult women and appropriate obesity prevention strategies must be taken. With reference to being needed exploring the obesity perception, its causes, and impact as well as countermeasures strategies based on the needs of the society itself. The study was intended to explore the society perception regarding obes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
0
3
0
1
Order By: Relevance
“…These studies have found gaps in knowledge about ideal body weight, dietary practices to be followed and misconceptions about physical activity. [ 30 31 32 33 34 ] Even though women are aware about the negative impact of gaining weight, they face various physical, social and psychological barriers that impede their own ability to put forth the effort required for losing the excess weight. This eventually leads to frustration of weight loss-regain and paves way for distorted body image and unhealthy lifestyle practices.…”
Section: Resultsmentioning
confidence: 99%
“…These studies have found gaps in knowledge about ideal body weight, dietary practices to be followed and misconceptions about physical activity. [ 30 31 32 33 34 ] Even though women are aware about the negative impact of gaining weight, they face various physical, social and psychological barriers that impede their own ability to put forth the effort required for losing the excess weight. This eventually leads to frustration of weight loss-regain and paves way for distorted body image and unhealthy lifestyle practices.…”
Section: Resultsmentioning
confidence: 99%
“…Helen Keller learned from Sullivan to read and write in Braille and to use hand signals of the deaf and mute, which she could understand only by touch. Finally emerging successful through all odds, she became the first disabled student to graduate in Bachelor of Arts from Radcliff College in 1904 and write a book (Könönen, 2014;Wiardani et al, 2018;Agra et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The method used in this study is a qualitative descriptive method of research. Qualitative descriptive research performs careful measurements of certain social phenomena by developing concepts and collecting facts (Sutapa et al, 2017;Wiardani et al, 2018). According to Moleong "qualitative research is a study that intends to understand the phenomenon of what is experienced by the subjects of research, e.g.…”
Section: Methodsmentioning
confidence: 99%